2021
DOI: 10.3390/children8040277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutrition, and Physical Activity Habits and Perceptions on Body Mass Index (BMI) in Children Aged 12–15 Years: A Cross-Sectional Study Comparing Boys and Girls

Abstract: Background: The aim of the present study was to examine the effects of socioeconomic status, nutrition and physical activity lifestyle habits and perceptions on Body Mass Index (BMI) in children aged 12–15 years in Greece. Furthermore, to compare the difference between the two sexes. Methods: This is a cross-sectional study conducted on a representative secondary school cohort that included 5144 subjects, aged 12 to 15 years. Students and their parents filled in validated questionnaires evaluating socioeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
1
9
0
1
Order By: Relevance
“…These results are in line with comparable studies reporting that the percentage of overweight boys tends to be nearly three times higher than girls [ 54 ]. A cross-sectional study by Carayanni et al [ 55 ] with a sample of 5144 children aged 12 to 15 years old found that boys are 2.9 times more likely to be overweight or obese compared to girls, which confirms the present findings. However, inconsistent results are shown in similar studies by Lisowski et al [ 56 ], who reported no sex differences in the prevalence of overweight in children, and by Kantanista et al [ 57 ], indicating BMI may not be a significant factor for boys or girls when planning health-focused PA programs in adolescents aged 14 to 16 years old.…”
Section: Discussionsupporting
confidence: 89%
“…These results are in line with comparable studies reporting that the percentage of overweight boys tends to be nearly three times higher than girls [ 54 ]. A cross-sectional study by Carayanni et al [ 55 ] with a sample of 5144 children aged 12 to 15 years old found that boys are 2.9 times more likely to be overweight or obese compared to girls, which confirms the present findings. However, inconsistent results are shown in similar studies by Lisowski et al [ 56 ], who reported no sex differences in the prevalence of overweight in children, and by Kantanista et al [ 57 ], indicating BMI may not be a significant factor for boys or girls when planning health-focused PA programs in adolescents aged 14 to 16 years old.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies demonstrated a higher prevalence of overweight in girls than in boys [ 59 , 60 ]. However, the study by Carayanni et al (2021) did not confirm this relationship [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breakfast is considered to be of major importance; an ideal breakfast should contain low-fat milk/milk-derived products, unrefined grains, and fresh fruit/fruit juice [ 23 ]. Systematic breakfast consumption has a protective effect against obesity [ 24 ], is positively associated with school performance [ 25 ] and better quality of life [ 26 ]. In addition, Ferrer-Cascales et al [ 27 ] revealed that adolescents who consumed more nutritious breakfasts had a better HRQoL and less stress and feeling of depression.…”
Section: Introductionmentioning
confidence: 99%